High-performance self-hardening iron-based shear blade material and preparation method thereof

The development of a high-performance self-hardening iron-based cutting blade material with specific chemical composition and micro-arc oxidation processing addresses the wear and deformation issues in scrap steel processing, achieving enhanced mechanical and wear resistance for efficient processing.

CN119663100APending Publication Date: 2025-03-21JIYUAN VOCATIONAL & TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775860.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing cutting tools used for processing scrap steel suffer from rapid wear and deformation due to the varied thickness and irregular shapes of scrap steel, along with embedded cement, sand, and high-strength steel rods, leading to increased production costs and cycle times.

Method used

A high-performance self-hardening iron-based cutting blade material with specific chemical composition (C 3.0%~4.0%, Si 2.0%~3.0%, P 2.0%~4.0%, Co 0.5%~1.5%, Mo 0.5%~1.5%, and the rest Fe) is developed, which undergoes melting and micro-arc oxidation processing to enhance mechanical and wear resistance.

Benefits of technology

The resulting cutting blade material achieves a Rockwell hardness of HRC65 and significant reduction in wear, offering improved mechanical and wear resistance for efficient scrap steel processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171423140000101
    Figure BDA0005171423140000101
  • Figure BDA0005171423140000141
    Figure BDA0005171423140000141
Patent Text Reader

Abstract

The invention relates to the technical field of shearing tool materials, and discloses a high-performance self-hardening iron-based shearing blade material and a preparation method. The invention discloses a high-performance self-hardening iron-based shear blade material which comprises the following chemical component raw materials: 3.0%-4.0% of C, 2.0%-3.0% of S i, 2.0%-4.0% of P, 0.5%-1.5% of Co, 0.5%-1.5% of Mo and the balance of Fe. The Rockwell hardness of the high-performance self-hardening iron-based shear blade material can reach HRC65, the 60min abrasion weight loss can reach 119 mg, and the high-performance self-hardening iron-based shear blade material has high mechanical performance and abrasion resistance and can be applied to preparation of shear blades.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shearing tool materials, and in particular to a high-performance self-hardening iron-based shearing blade material and a preparation method thereof. Background Art

[0002] my country is the world's largest producer and consumer of scrap steel. With the vigorous development of the steel industry, self-produced scrap steel cannot meet the production demand, and the amount of recycled scrap steel is increasing year by year. The main sources of recycled scrap steel are processing scrap steel and depreciation scrap steel, among which depreciation scrap steel is the largest source of recycled scrap steel and the most difficult to recycle.

[0003] After the scrap steel enters the site, most of it needs to be shortened by hydraulic shears (crocodile shears, gantry shears and box shears, etc.) or combined punching and shearing machines. Since the scrap steel sheets are uneven in thickness and irregular in shape, they are often attached with a small amount of cement and sand, especially the bars in the scrap steel, most of which are rebars scrapped from construction, including illegally produced unbranded and miscellaneous steel bars, which are brittle and hard with high hardness. When using crocodile shears and combined punching and shearing machines to shorten them, the working conditions are very harsh. The existing shear blades are usually made of heat-treated T10 steel. This type of shear blade wears quickly and is prone to curling, deformation, and even collapse. These problems seriously restrict production costs and production cycles. Therefore, the development of a self-hardening iron-based shear blade material with high mechanical properties and wear resistance has become a technical problem that needs to be urgently solved by technicians in this field. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance self-hardening iron-based shear blade material and a preparation method thereof. The high-performance self-hardening iron-based shear blade material has high mechanical properties and wear resistance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A high performance self-hardening iron-based shear blade material comprising the following chemical composition raw materials:

[0008] C 3.0%~4.0%, Si 2.0%~3.0%, P 2.0%~4.0%, Co 0.5%~1.5%, Mo0.5%~1.5%, and the balance is Fe.

[0009] The second technical solution of the present invention:

[0010] The method for preparing the high-performance self-hardening iron-based shear blade material comprises the following steps:

[0011] 1) Weigh each raw material according to the above chemical composition;

[0012] 2) mixing the raw materials weighed in step 1) and smelting them to obtain a molten liquid metal mixture;

[0013] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0014] 4) placing the iron-based alloy obtained in step 3) in a NaOH solution, performing micro-arc oxidation treatment on the iron-based alloy, washing, and drying to obtain the high-performance self-hardening iron-based shear blade material.

[0015] Furthermore, in step 2), the smelting is specifically: smelting at 1500-1600° C. for 40-60 min.

[0016] Furthermore, in step 2), before the smelting, it is necessary to preheat at 800-900° C. for 10-20 minutes.

[0017] Furthermore, in step 4), the concentration of the NaOH solution is 0.1 mol·L -1 .

[0018] Furthermore, in step 4), the parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 to 40 min, current density 10 to 15 A·dm -2 .

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The high-performance self-hardening iron-based shear blade material provided by the present invention has a Rockwell hardness of up to HRC65 and a weight loss of up to 119 mg after 60 minutes of wear. It has high mechanical properties and wear resistance and can be used in the preparation of shear blades. DETAILED DESCRIPTION

[0021] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0022] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0023] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0024] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0025] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0026] In the present invention, the professional term "chemical composition" is measured in terms of mass percentage.

[0027] The raw materials used in the following examples are all commercially available.

[0028] In the following embodiment, a method for preparing a high-performance self-hardening iron-based shear blade material comprises the following steps:

[0029] 1) Weigh each raw material according to the following chemical composition:

[0030] C 3.0%~4.0%, Si 2.0%~3.0%, P 2.0%~4.0%, Co 0.5%~1.5%, Mo0.5%~1.5%, the balance is Fe;

[0031] 2) mixing the raw materials weighed in step 1), preheating at 800-900° C. for 10-20 min, and then smelting at 1500-1600° C. for 40-60 min to obtain a molten liquid metal mixture;

[0032] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0033] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0034] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10-40 min, current density 10-15 A·dm -2 .

[0035] Example 1

[0036] A high performance self-hardening iron-based shear blade material

[0037] 1) Weigh each raw material according to the following chemical composition:

[0038] C 3.0%, Si 2.0%, P 2.0%, Co 0.5%, Mo 0.5% and Fe balance;

[0039] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0040] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0041] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0042] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0043] Example 2

[0044] A high performance self-hardening iron-based shear blade material

[0045] 1) Weigh each raw material according to the following chemical composition:

[0046] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0047] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0048] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0049] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0050] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0051] Example 3

[0052] A high performance self-hardening iron-based shear blade material

[0053] 1) Weigh each raw material according to the following chemical composition:

[0054] C 4.0%, Si 3.0%, P 4.0%, Co 1.5%, Mo 1.5% and Fe balance;

[0055] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0056] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0057] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0058] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0059] Comparative Example 1

[0060] Iron-based shear blade material

[0061] 1) Weigh each raw material according to the following chemical composition:

[0062] C 2.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0063] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0064] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0065] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0066] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0067] Comparative Example 2

[0068] Iron-based shear blade material

[0069] 1) Weigh each raw material according to the following chemical composition:

[0070] C 4.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0071] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0072] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0073] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0074] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0075] Comparative Example 3

[0076] Iron-based shear blade material

[0077] 1) Weigh each raw material according to the following chemical composition:

[0078] C 3.5%, Si 1.5%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0079] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0080] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0081] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0082] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0083] Comparative Example 4

[0084] Iron-based shear blade material

[0085] 1) Weigh each raw material according to the following chemical composition:

[0086] C 3.5%, Si 4.5%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0087] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0088] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0089] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0090] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0091] Comparative Example 5

[0092] Iron-based shear blade material

[0093] 1) Weigh each raw material according to the following chemical composition:

[0094] C 3.5%, Si 2.8%, P 1.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0095] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0096] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0097] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0098] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0099] Comparative Example 6

[0100] Iron-based shear blade material

[0101] 1) Weigh each raw material according to the following chemical composition:

[0102] C 3.5%, Si 2.8%, P 5.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0103] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0104] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0105] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0106] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0107] Comparative Example 7

[0108] Iron-based shear blade material

[0109] 1) Weigh each raw material according to the following chemical composition:

[0110] C 3.5%, Si 2.8%, P 3.0%, Mo 1.0% and Fe balance;

[0111] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0112] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0113] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0114] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0115] Comparative Example 8

[0116] Iron-based shear blade material

[0117] 1) Weigh each raw material according to the following chemical composition:

[0118] C 3.5%, Si 2.8%, P 3.0%, Co 2.0%, Mo 1.0% and Fe balance;

[0119] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0120] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0121] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0122] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0123] Comparative Example 9

[0124] Iron-based shear blade material

[0125] 1) Weigh each raw material according to the following chemical composition:

[0126] C 3.5%, Si 2.8%, P 3.0%, Co 1.0% and Fe balance;

[0127] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0128] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0129] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0130] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0131] Comparative Example 10

[0132] Iron-based shear blade material

[0133] 1) Weigh each raw material according to the following chemical composition:

[0134] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 2.0% and Fe balance;

[0135] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0136] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0137] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0138] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 min, current density 10 A·dm -2 .

[0139] The mechanical properties and wear resistance of the iron-based shear blade materials prepared in Examples 1 to 3 and Comparative Examples 1 to 10 were tested. The results of the mechanical properties and wear resistance tests are shown in Table 1.

[0140] Table 1 Mechanical properties and wear resistance test results

[0141]

[0142] It can be seen from the data in Table 1 that the high-performance self-hardening iron-based shear blade material provided by the present invention has high mechanical properties and wear resistance; and changing the chemical composition of the high-performance self-hardening iron-based shear blade material will reduce the mechanical properties and wear resistance of the self-hardening iron-based shear blade material to a certain extent.

[0143] Example 4

[0144] A high performance self-hardening iron-based shear blade material

[0145] 1) Weigh each raw material according to the following chemical composition:

[0146] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0147] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0148] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0149] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0150] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 25 min, current density 10 A·dm -2 .

[0151] Example 5

[0152] A high performance self-hardening iron-based shear blade material

[0153] 1) Weigh each raw material according to the following chemical composition:

[0154] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0155] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0156] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0157] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0158] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 40 min, current density 10 A·dm -2 .

[0159] Example 6

[0160] A high performance self-hardening iron-based shear blade material

[0161] 1) Weigh each raw material according to the following chemical composition:

[0162] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0163] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0164] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0165] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0166] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 25 min, current density 13 A·dm -2 .

[0167] Example 7

[0168] A high performance self-hardening iron-based shear blade material

[0169] 1) Weigh each raw material according to the following chemical composition:

[0170] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0171] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0172] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0173] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0174] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 25 min, current density 15 A·dm -2 .

[0175] Comparative Example 11

[0176] A high performance self-hardening iron-based shear blade material

[0177] 1) Weigh each raw material according to the following chemical composition:

[0178] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0179] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0180] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0181] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0182] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 5 min, current density 13 A·dm -2 .

[0183] Comparative Example 12

[0184] A high performance self-hardening iron-based shear blade material

[0185] 1) Weigh each raw material according to the following chemical composition:

[0186] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0187] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0188] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0189] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0190] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 50 min, current density 13 A·dm -2 .

[0191] Comparative Example 13

[0192] A high performance self-hardening iron-based shear blade material

[0193] 1) Weigh each raw material according to the following chemical composition:

[0194] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0195] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0196] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0197] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0198] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 25 min, current density 5 A·dm-2 .

[0199] Comparative Example 14

[0200] A high performance self-hardening iron-based shear blade material

[0201] 1) Weigh each raw material according to the following chemical composition:

[0202] C 3.5%, Si 2.8%, P 3.0%, Co 1.0%, Mo 1.0% and Fe balance;

[0203] 2) mixing the raw materials weighed in step 1), preheating at 850° C. for 15 min, and then smelting at 1560° C. for 50 min to obtain a molten liquid metal mixture;

[0204] 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy;

[0205] 4) The iron-based alloy obtained in step 3) is placed in a concentration of 0.1 mol·L -1 The iron-based alloy is subjected to micro-arc oxidation treatment in a NaOH solution, washed, and dried to obtain the high-performance self-hardening iron-based shear blade material;

[0206] The parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 25 min, current density 20 A·dm -2 .

[0207] The mechanical properties and wear resistance of the iron-based shear blade materials prepared in Examples 4 to 7 and Comparative Examples 11 to 14 were tested. The results of the mechanical properties and wear resistance tests are shown in Table 1.

[0208] Table 2 Mechanical properties and wear resistance test results

[0209]

[0210] It can be seen from the data in Table 2 that the high-performance self-hardening iron-based shear blade material provided by the present invention has a Rockwell hardness of up to HRC65 and a 60-minute wear weight loss of up to 119 mg, and has high mechanical properties and wear resistance. However, changing the oxidation time and current density of the micro-arc oxidation treatment will reduce the mechanical properties and wear resistance of the self-hardening iron-based shear blade material to a certain extent.

[0211] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high performance self-hardening iron-based shear blade material, characterized in that: Including the following chemical ingredients: C 3.0%~4.0%, Si 2.0%~3.0%, P 2.0%~4.0%, Co 0.5%~1.5%, Mo0.5%~1.5%, and the balance is Fe.

2. A method for preparing a high-performance self-hardening iron-based shear blade material as claimed in claim 1, characterized in that: The following steps are involved: 1) Weigh each raw material according to the above chemical composition; 2) mixing the raw materials weighed in step 1) and smelting them to obtain a molten liquid metal mixture; 3) pouring the molten liquid metal mixture obtained in step 2) into a mold to obtain an iron-based alloy; 4) placing the iron-based alloy obtained in step 3) in a NaOH solution, performing micro-arc oxidation treatment on the iron-based alloy, washing, and drying to obtain the high-performance self-hardening iron-based shear blade material.

3. A preparation method according to claim 1, characterized in that: In step 2), the smelting is specifically: smelting at 1500-1600° C. for 40-60 min.

4. A preparation method according to claim 1, characterized in that: In step 2), before smelting, it is necessary to preheat at 800-900°C for 10-20 minutes.

5. A preparation method according to claim 1, characterized in that: In step 4), the concentration of the NaOH solution is 0.1 mol·L -1 .

6. A preparation method according to claim 1, characterized in that: In step 4), the parameters of the micro-arc oxidation treatment are: frequency 400 Hz, duty cycle 20%, oxidation time 10 to 40 min, current density 10 to 15 A·dm -2 .